Identificação das espécies do gênero cichla (perciformes; cichlldae) da coleção ictiológica do Museu Paraense Emílio Goeldi (MPEG) - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2008)
The Cichlidae family is a taxon with great specific diversity, being present in the Americas, Africa, Madagascar, southern coast of India, Sri Lanka and the Middle East. Among the most relevant species are those belonging to the genus Cichla, which is characterized by the presence of dark vertical bars, continuous or discontinuous lateral line, 15-16 hard rays on the dorsal fin and relatively high body. Due to specific identification problems, only six species were described (C. intermedia, C. monoeulus, C. oeellaris, C. orinoeensis, C. temensis and C. nigromaeulata). nigromaeulata), however, after the recent works related to the genus, nine new species were added (C. kelberi, C. pleiozona, C. piquiti, C. thyrorus, C. jariina, C. vazzoleri, C. pinima, C. mirianae, C. melaniae). This work aimed to review and re-identify the specimens deposited in the ichthyological collection of the Museu Paraense Emílio Goeldi (MPEG). The specimens were morphologically analyzed with the aid of a stereoscopic microscope and the measurements made with the aid of a caliper to the tenth of a millimeter. The identifications of all the batches were reviewed, nine of which were previously identified as e oeellarisconfound to be e monoeulus(n=4), C. nigromaeulata(n= 1), C. melanie(n=2), e pinima(n= 1) and C. pleizona(n= 1). Among nine lots of C. temensis, four lots were re-identified as C. pinima and among seven lots of C. monoeulus, only one was re-identified with C. vazzoleti. From a total of 32 lots identified as Cichla sp., only one lot was identified as C. ocellaris, and the rest identified among C. monoeulus (n=8), and vazzoleri (n=9), C. orinoeensis (n=3), C. pinima (n=5), C. temensis (n=2), C.piquiti (n=2), C. melaniae (n= 1) C. kelberi (n= 1). There were changes in the geographical distribution of four species, among them C.melanie, which according to the specialized literature occurs only in the lower Xingo River. However, according to the recent identification of these lots there is an expansion of the distribution of C. melanie occurring in the Amazon and Tocantins rivers. The present study analyzed in detail the species belonging to the genus Cichle, promoting the updating of all lots of this genus deposited in the ichthyological collection of MPEG, according to the specialized literature.
Identification of species of the genus cichla (perciformes; cichlldae) from the ichthyological collection of the Museu Paraense Emílio Goeldi (MPEG).
Keywords: Taxonomia; Cichlidae; Cichla; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES